Cleft palate in Pierre Robin syndrome: A Review of 7 cases - A.D.C. Opango; M.S.K. Hattab; Y. Bennaoui; D. Ndélafei; Z. Aziz; N. Mansouri-Hattab (Elsevier, 2023)
Introduction: Pierre Robin syndrome is a malformative sequence associating retrognathism, glossoptosis and a median cleft palate which is usually large. This poses the problem of its therapeutic management. Purpose: To show the approach of the Stomatology and Maxillofacial Surgery Department of the Mohammed VI University Hospital in the management of cleft palate in Pierre Robin syndrome.This was a retrospective study, covering 5 years, which allowed us to include 7 cases of cleft palate in Pierre Robin syndrome. Our study parameters were epidemiological, clinical, therapeutic and evolutionary. Results: The average age of our patients, at the time of the 1st consultation, was 4 months. There was a slight male predominance with a sex ratio = 1.3. The patients presented a U-shaped cleft in 57.1% of cases, and a V-shaped cleft in 42.9% of cases. Three patients underwent a one-stage closure by velopalatoplasty using the Von Langenbeck technique. Four patients underwent a 2-stage closure, i.e., intravascular veloplasty in the first stage, followed by closure of the residual cleft palate in the second stage. The results were satisfactory. A palatal fistula was noted in 42.8% of cases, which was managed secondarily. Conclusion: The management of cleft palate in Pierre Robin syndrome is a real challenge for the maxillofacial surgeon.